The Effect Of Kegel Exercise On The Healing Of Perineal Wounds In Post Partum Women At The Biadan Novi Lintas Timur Clinic, Panyabungan District, Mandailing Natal Regency - Ester Selfia Napitupulu; Ferika Desi (Sean Institute, 2022)
Childbirth often results in injuries to the perineum, either injuries resulting from vaginal tears or episiotomy, which causes pain in the scar from the birth canal tear. Kegel exercises can restore flexibility to the perineal muscles and Kegel exercises are easy to do and provide relaxation and reduce anxiety and thus the intensity of pain. The aim of this study was to determine the effect of Kegel exercises on perineal wound healing in post partum mothers. The design of this research is quantitative research using a pre-post test design research design approach. The population and sample for this study were 25 post partum mothers at the Novi Midwife Clinic. Data collection uses observation sheets. Data analysis used the Wilcoxon test. The research results showed that the average healing of perineal wounds in postpartum mothers before and after doing Kegel exercises experienced a significant increase, where before doing Kegel exercises the results of observations of perineal wound healing were in moderate and poor conditions, namely 9.48. Meanwhile, after carrying out Kegel exercises, the observation results for perineal wound healing were in good and moderate condition, namely with an average observation of 6.04. The existence of significant changes in perineal wound healing before and after Kegel exercise can be determined using the Wilcoxon test with a value of p= 0.000 (p<0.05). These results prove that Kegel exercise has been proven to be effective in accelerating the healing of perineal wounds in postpartum mothers at the clinic. Novi Lintas Timur midwife, Panyabungan District, Mandailing Regency, Christmas 2022.